Analysis of Occupational Safety and Health Management System (SMK3) on Workers In Cikeruh Majalengka Bridge Construction Project - Sutanto, Pachri; Pitaloka, Renata; Fatmala, Lia; Rozy, Nikko (Green Publisher Indonesia, 2025)
The implementation of safety and health (OSH) systems in the work environment is a crucial component for the running of a business entity, because the consequences of accidents can have a detrimental impact on the workforce and the institution. This study was conducted to evaluate how OHS affects the level of worker productivity. A quantitative approach is the method used by collecting primary data through distributing questionnaires to 35 workers at the Cikeruh Majalengka Bridge Construction Project. Data analysis was carried out using IBM SPSS 26.0 for Windows, by conducting an Instrument Test consisting of Validity Test and Reliability Test. The variables studied consisted of four independent variables: Planning (X1), Organization (X2), Actuating (X3), Controlling (X4) and one dependent variable, namely Worker Productivity (Y). The results showed that Planning has a positive effect on productivity with an average value of 1.98, Organization 2.0, Actuating 1.78, and Controlling 1.94. The four independent variables as a whole have an average value of 1.92 which indicates a positive influence on worker productivity on the project, because it is in the interval class 1.6 ≥ x ≤ 2.0. This proves that factors such as planning, organization, implementation, and supervision play a significant role in increasing worker productivity on the Majalengka Cikeruh Bridge Construction Project.